Looting of Antiquities in Jordan: A General Overview - Al Manaser, Ali; Al-Tell, Yazan (مركز عبد الرحمن السديري الثقافى, 2020)
يهدف هذا البحث لتقصي مسألة أعمال نهب الآثار وسرقتها، والتي ما تزال منتشرة في الأردن؛ إذ يناقش أعمال نهب الآثار وتسويقها، من خلال مقابلات شخصية مع عديد من الأشخاص الذين امتهنوا هذه الأعمال؛ ويتناول البحث كذلك دور كل من الإنترنت والدين والعرف، فيما يتعلق بانتشار الحفريات الأثارية غير القانونية في الأردن. إضافة إلى ذلك، يناقش البحث الرموز والإشارات التي تدل على "الكنز" بالتفصيل. يشتمل البحث على ٧٥ مقابلة أجريت مع أفراد انخرطوا في تسويق الآثار والحفريات غير القانونية، يقطنون السلط وعجلون وعمان؛ إذ تبين أن الكسب المادي هو أهم الدوافع لممارسة نهب الآثار، والقيام بأعمال التنقيب غير القانونية.
The aim of this research is to investigate the issue of looting, which unfortunately remains prevalent in Jordan. The research discusses the marketing of antiquities and looting in Jordan through personal interviews with a number of individuals who are engaged in this activity. There is also an analysis of the role of the internet, religion, and tradition in Jordan in connection with the spread of illegal excavations; symbols and signs that purport to direct to treasure are discussed in detail. This research includes an in-depth analysis of 75 other interviews carried out with individuals involved in the marketing of antiquities and illegal excavation who reside in As-Salt, 'Ajloun, and Amman. As a result of their background, they give a good sense of the motives behind the practice of looting and the factors that directly contribute to the activity, most of which being financial.
Keywords: سرقة الآثار -- الممتلكات الثقافية -- التراث الحضاري -- الأردن